Framework for the adoption of blockchain in maritime cold chains - Johannes Schnelle; Meike Schröder; Wolfgang Kersten (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: This analysis aims to develop a conceptual framework for the adoption of blockchain-based solutions in maritime logistics. Using the application area of maritime cold chains, we examine which characteristics are crucial for the use of blockchain and which requirements need to be met for adoption. Methodology: The method follows the approach of empirical data collection with expert interviews. From the interviews, a conceptual framework for the implementation of blockchain-based solutions into the maritime cold chain was developed using qualitative content analysis. Findings: Within the interview study, we identified the potential for the use of blockchain in the maritime cold chain in providing an open and neutral platform in which data from different actors are securely integrated. The adoption of the technology requires considerations regarding economic evaluation, stakeholder integration, process development, data security, and legal compliance. Originality: The implementation of blockchain in the maritime supply chain is a well-studied research area, but there remains a lack of the integration of data from the material flow such as sensor data. This research aims to fill this gap.
urn:nbn:de:gbv:830-882.0200544; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Artificial Intelligence; Blockchain